2019
DOI: 10.1029/2018jd029420
|View full text |Cite
|
Sign up to set email alerts
|

Vb Cyclones Synchronized With the Arctic‐/North Atlantic Oscillation

Abstract: Vb cyclones typically emerge in the Western Mediterranean and propagate to the Northeast into Central Europe. This paper explores the temporal characteristics of Vb cyclone occurrence based on cyclone tracks identified at the atmospheric levels of Z700 and sea level pressure, using JRA‐55 reanalysis data for the period 1959–2015. The risk of Vb occurrence was significantly high in the 1960s and has remained at a lower level since then. Vb cyclones do not occur fully randomly according to a Poisson point proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 139 publications
0
35
0
Order By: Relevance
“…There has indeed been a clear upward step in the winter NAO index in the 1970s (Hurrell et al, 2003 Hurrell & Deser, 2009), as demonstrated, for example, by the statistical analysis of Gómez‐Martínez et al (2018) (see their Figure 7). The storm track analyses of Hofstätter and Blöschl (2019) suggest that cyclones in Europe are more generally synchronized with the NAO and the Arctic Oscillation. These shifts in precipitation then impact on flood occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…There has indeed been a clear upward step in the winter NAO index in the 1970s (Hurrell et al, 2003 Hurrell & Deser, 2009), as demonstrated, for example, by the statistical analysis of Gómez‐Martínez et al (2018) (see their Figure 7). The storm track analyses of Hofstätter and Blöschl (2019) suggest that cyclones in Europe are more generally synchronized with the NAO and the Arctic Oscillation. These shifts in precipitation then impact on flood occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…3c) highlighted are 20-year periods with particularly high ( P + 1947-1966 and 1999-2018) and low ( P − 1975-1994) interannual variability; the dashed line indicates the zero-line for the standardized indicators MFI and PER and the mean of P for the period 1901-2018 attributed to a positive phase of the Scandinavian Pattern (Comas-Bru and Hernández 2018) related to blocking over Scandinavia. Hofstätter and Blöschl (2019) showed that Scandinavian blocking is often associated with negative North Atlantic Oscillation (NAO) and Arctic Oscillation (AO) conditions. These in turn have the potential to trigger cyclogenesis in the Western Mediterranean and persistent cyclonic circulation which frequently causes heavy rain in the Alpine region with potential for large scale flooding (Hofstätter et al 2018).…”
Section: Regional and Local Scale Driversmentioning
confidence: 99%
“…The thick lines show the median, and the shaded areas show the 10th to 90th percentile spread. servations (Contractor et al, 2015;Hofstra et al, 2010;Peleg et al, 2018;Prein and Gobiet, 2017;Tozer et al, 2012). In addition to the high resolution, the regular distribution of WEGN gauges enables generating gridded rainfall fields that are homogeneous in space and, consequently, robustly assess uncertainty in rare and extreme rainfall represented in the data.…”
Section: Impact Of Spatial Aggregation On Extreme Rainfallmentioning
confidence: 99%
“…Often, rainfall data are required as areal estimates at the scale of interest, for instance, at grid or catchment scales. Point measurements from in situ S. O and U. Foelsche: Spatial uncertainty of heavy rainfall gauge observations are spatially aggregated or interpolated to estimate the areal distribution of rainfall, and hence the accuracy of areal rainfall data is highly dependent on spatiotemporal variability in rainfall events and density of observation points (Girons Lopez et al, 2015;Hofstra et al, 2010;Villarini et al, 2008;Wood et al, 2000). This limits the understanding of fine-scale rainfall processes, particularly of extreme events (Sillmann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation